Hubungan Durasi Cross-Legged Sitting (CLS) dengan Gejala Nyeri Panggul pada Mahasiswi Fisioterapi Fakultas Kedokteran Universitas Udayana - Victoria Putri Jegaut; Gede Parta Kinandana; Ni Luh Putu Gita Karunia Saraswati; Sayu Aryantari Putri Thanaya (KOLONI, 2026)
Unergonomic sitting positions, especially cross-legged sitting (CLS), are often maintained by female students in academic activities and have the potential to cause musculoskeletal complaints such as pelvic pain. This study aims to analyze the relationship between CLS duration and pelvic pain symptoms in female physiotherapy students. This study used an observational cross-sectional analytical design with 100 respondents aged 18–22 years old selected based on inclusion criteria. Data regarding CLS habits and pelvic pain symptoms were collected through questionnaires and analyzed using Spearman's correlation test. The results showed that the majority of respondents sat CLS for less than 15 minutes, some for 15–30 minutes, and a little more than 30 minutes, with pelvic pain complaints varying from mild to moderate categories. Statistical analysis showed a significant relationship between CLS duration and pelvic pain (p < 0.001; ρ = 0.543), with moderate strength and positive direction. There is a significant relationship between CLS duration and pelvic pain, indicating that the longer the CLS position is maintained, the greater the tendency to experience pelvic pain symptoms.